Implementation of Total Quality Management (TQM) at Tunas Bangsa Primary School (SD Tunas Bangsa) in Kubu Raya Regency - Rahmad Wibowo; Syukri Syukri; Sukmawati Sukmawati (STKIP Singkawang, 2019)
The implementation of TQM at SD Tunas Bangsa Kubu Raya does not always run smoothly. There are things that hinder the implementation. However, even though there are obstacles to the implementation of the TQM, the number of students has increased in the last 5 years. The purpose of this study was to describe (1) Quality leadership at SD Tunas Bangsa Kubu Raya; (2) Quality teamwork at SD Tunas Bangsa Kubu Raya; (3) Efforts to build a quality culture at SD Tunas Bangsa, and (4) Supporting and inhibiting factors for TQM implementation at SD Tunas Bangsa Kubu Raya. This study uses a qualitative approach with a type of descriptive research. Data collection techniques in this study were carried out by observation techniques, direct communication techniques, and documentation techniques. The results of this study include (1) Quality leadership carried out by school leaders namely Principal, Deputy Principal, and PYP Curriculum Coordinator based on teamwork, namely the leadership team and the teacher team; (2) Teamwork at SD Tunas Bangsa Kubu Raya consisting of a leadership team and teacher team is considered good because team members develop favorable team behavior and work collaboratively both in making plans and implementing them; (3) Efforts to build a quality culture are sought by leaders and teachers; (4) The supporting factor for the implementation of TQM at SD Tunas Bangsa Kubu Raya is a strong commitment from the leadership and senior teachers. While the inhibiting factor is new teachers need time to understand and be able to perform according to IB quality standards and school standards.